To succeed in China, focus on interests rather than rules - Michael J. Enright (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Interests, not rules have driven China's approach toward inward FDI. As President Xi Jinping consolidates power, China becomes more assertive on the world stage, and Chinese companies become more capable, foreign companies will increasingly have to demonstrate the specific value they generate for China to access China opportunities.
Keywords: 330